FINANCIAL LITERACY, LIFESTYLE, CONSUMPTION BEHAVIOR K-POP FANS IN COVID-19 PANDEMIC WITH RELIGIOSITY AS MODERATING VARIABLE - Putri Vita Nadia (Jurnal Akuntansi, 2022)
Increased consumption of Korean goods and products as well as travel to South Korea along with K-Pop which is increasingly known to the world. This consumption behavior, one of which can be seen through the lifestyle of Korean idol fans. Unfortunately, since the COVID-19 pandemic, many loss-making companies are no exception to entertainment agencies in Korea. However, the agencies that house K-pop idols are not lost their minds and are starting to build innovations by releasing a lot of content remotely. Although K-Pop content has grown and can be reached online, in fact not all K-pop fans can consume the content as before. This is due to a decrease in their pocket money or income during the COVID-19 pandemic. The study aims to find out whether the quality of financial literacy, lifestyle, and religiosity of K-Pop fans can affect their consumption behavior in the era of the COVID-19 pandemic. This research uses quantitative descriptive methods. The population of the study was a follower of the @everydays_quran Twitter account of 472 people and sampled 217 people with simple random sampling techniques using the Slowin formula. The data was obtained through the results of questionnaires distributed through Google Form. This study uses Partial Least Square (PLS) analysis techniques with the help of SmartPLS 3 software. The results of this study showed that 1) financial literacy had a significant effect on consumption behavior, 2) lifestyle had a significant effect on consumption behavior, 3) religiosity had no significant effect on consumption behavior, 4) religiosity could not moderate the influence of financial literacy on consumption behavior, and 5) religiosity could moderate lifestyle influences on consumption behavior.